Impact on colorectal cancer pathology reporting practice of migration from TNM 5 to TNM 8. Issue 2 (21st July 2020) - Loughrey, Maurice B; Kent, Olivia; Moore, Michelle; Coghlin, Caroline; Kelly, Paul; McVeigh, Gerard; Coleman, Helen G
Abstract: Aims: The introduction of TNM 8 into UK pathology practice in January 2018 considers tumour deposits in colorectal cancer staging for the first time. The impact of this new classification on pathology reporting practices has yet to be evaluated. Methods and results: A clinical audit was conducted, comparing consecutive colorectal cancer resection specimens reported under TNM 5 classification guidelines in 2017 ( n  = 177) and TNM 8 guidelines in 2018 ( n  = 234). Tumour features (venous invasion, perineural invasion, lymph node metastatic disease, tumour deposits) and changes in reporting practices were evaluated among four specialist gastrointestinal pathologists working within a large pathology department. Adoption of TNM 8 practice led to an approximate doubling in the use of ancillary stains (41.0% of TNM 8 versus 22.0% of TNM 5 cases, P  < 0.001) to help evaluate tumours. A narrowing of the range between pathologists was observed in reporting cases as having one or more form of regional, extramural, discontinuous tumour (TNM 5 range = 50.0–79.0%, TNM 8 range = 57.8–65.7%), with no change in the overall proportion of cases reported as such (62.7% versus 62.4%, P  = 0.95). However, significant interobserver variation in reporting rates for individual parameters remained. Conclusion: TNM 8 colorectal cancer staging offers potentially greater reproducibility in pathology reporting of regional, extramural, discontinuous disease with similar proportions of patients reported as having one or more of these forms of tumour spread compared with TNM 5. Further guidance in defining individual features is required to reduce interobserver variation in pathology assessments and to help elucidate the clinical significance of each parameter.